Evaluating the Relationship Between Talent Management, Motivation, and Career Development on Employee Productivity - Hodi; Murcahyanto, Hary; Sukardi; Suyitno (Journal Management & Economics Review (JUMPER), 2025)
This study examines the relationship between talent management, motivation, and career development on employee productivity in organizational settings. As businesses face increasing competition and workforce challenges, understanding how human resource practices influence performance has become essential. Using a quantitative research design, data were collected from 250 employees across various industries and analyzed through multiple linear regression. The results reveal that talent management, motivation, and career development each have a significant and positive effect on employee productivity, with talent management emerging as the most influential factor. These findings highlight that effective talent management practices such as strategic recruitment, competency development, and employee retention can substantially enhance organizational performance. Motivation, encompassing both intrinsic and extrinsic dimensions, was also found to drive higher productivity by fostering engagement and commitment. Additionally, career development opportunities contribute to improved productivity by increasing employees’ sense of purpose, capability, and career satisfaction. The study underscores the importance of adopting an integrated human resource management approach that combines talent optimization, motivational support, and career growth initiatives. Practically, the results suggest that organizations seeking to improve productivity should invest in employee-centered policies that align professional development with organizational goals. Theoretically, this research extends existing knowledge by validating the combined impact of these three key HR factors on productivity within the modern workplace context.